2021
DOI: 10.1002/jlb.3ri1220-834r
|View full text |Cite
|
Sign up to set email alerts
|

The FasLane to ocular pathology—metalloproteinase cleavage of membrane-bound FasL determines FasL function

Abstract: Fas ligand (FasL) is best known for its ability to induce cell death in a wide range of Fas‐expressing targets and to limit inflammation in immunoprivileged sites such as the eye. In addition, the ability of FasL to induce a much more extensive list of outcomes is being increasingly explored and accepted. These outcomes include the induction of proinflammatory cytokine production, T cell activation, and cell motility. However, the distinct and opposing functions of membrane‐associated FasL (mFasL) and the C‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 153 publications
(196 reference statements)
0
4
0
Order By: Relevance
“…Because of the presence of TGF-, this difference was lost when tumors were grafted into the anterior chamber of the eye [108]. Because Marshak-Rothstein and colleagues have recently described the role of CD95L in ocular pathologies [109], we will not go into further details.…”
Section: Ocular Pathologiesmentioning
confidence: 99%
“…Because of the presence of TGF-, this difference was lost when tumors were grafted into the anterior chamber of the eye [108]. Because Marshak-Rothstein and colleagues have recently described the role of CD95L in ocular pathologies [109], we will not go into further details.…”
Section: Ocular Pathologiesmentioning
confidence: 99%
“…Currently, for the antagonistic effect of mFasL and sFasL in glaucoma, Gregory-Ksande and Marshak-Rothstein ( 148 ) suggested that sFasL competes with mFasL for binding to Fas, resulting in steric hindrance. However, except for the Met12 small-molecule inhibitor, the steric hindrance mechanism by which Met12 binds to Fas results in fewer receptors available for FasL binding, directly interfering with FasL binding to Fas ( 153 ).…”
Section: Regulators Of Apoptotic Pathway In Glaucomamentioning
confidence: 99%
“…Membrane-bound FasL (mFasL) induces apoptosis and promotes inflammation upon binding to Fas. By contrast, the soluble Fas-ligand (sFasL), which is formed by cleavage of the 103-137 amino acid region of mFasL by MMPs, blocks the apoptosis and inhibits inflammation (145)(146)(147)(148). Previous research has revealed that the sFas concentration in the aqueous humour is lower in patients with POAG than in control individuals, suggesting that a low level of sFas may provide an appropriate microenvironment for increased apoptosis of TM cells in glaucoma (149).…”
Section: Regulators Of Apoptotic Pathway In Glaucomamentioning
confidence: 99%
“…Moreover, epithelial cells of the cornea express nonclassical MHC class I molecules such as HLA-G [ 27 ], which constitutes the mechanism of immune response evasion and inhibition towards effector T cells and NK cells [ 28 ]. Many structures of the eye, including cornea, express the following immunomodulatory molecules: FasL [ 29 , 30 ], PD-L1 [ 31 ], GITRL [ 32 ], ICOSL [ 33 ], galectin-9 (Gal-9) [ 34 ], B7-H3 [ 3 ], CTLA-2 α [ 35 , 36 ], and membrane-bound complement regulatory proteins (CD59, CD55, and CD46) [ 22 ] ( Table 1 ).…”
Section: Immune Privilege Of the Eyementioning
confidence: 99%